Relationship of physical environment of public preschool classroom on children’s social interaction behaviour and spatial choice / Mansor Othman - Othman, Mansor (Institute of Graduate Studies, 2017)
A strong emphasis is put on preschool education programme by the Malaysian Ministry of Education (MOE). However, it leans more towards the non-physical rather than the physical aspects of preschools. There is a scarcity of local reference on children’s environment-behaviour studies, notably on the physical environment of preschool classroom and spatial behaviour. Therefore, this research aimed to investigate this relationship. The objectives of this study were to identify the current state of the physical environment of public preschool classrooms (through the teachers’ perceptions) and to establish the types of social interaction behaviour that the children engaged in (during free play) in their classrooms as located both in urban and non-urban areas. Their spatial choices were also observed. The preschool classrooms were spatially categorised into highly, moderately and poorly defined through the experts’ opinions survey. This study used the mixed method approach of questionnaire surveys and unobtrusive, non-participating observation and behavioural mapping methods. The questionnaire was adopted from Moore’s (1994, 2008) Children’s Physical Environment Rating Scale (CPERS) which was administered to 330 preschool teachers who attended a series of MOE workshops. The observations found that there exists five types of social interaction behaviour and spatial choices that 494 children aged 5 to 6 years old engaged in during free-play periods in their classrooms in 20 public urban and non-urban preschools in the state of Selangor. The spatialdefinition of classrooms in both locations was acquired through a directly distributed questionnaire survey to 40 interior architects...